Sequential inactivation of Escherichia coli in drinking water using low sonication frequency and chlorination - Vo Thi Le Ha
Some species of bacteria produce colonies and spores that can agglomerate in spherical clusters and thus protect organisms on the inside of the cluster against biocidal attack. Others have the ability to mutate, thus building up resistance to conventional biocides (e.g., chlorine). One alternative method to solve the problems is the use of power ultrasound, either alone or in combination with chlorination. Ultrasound is able to inactivate bacteria and deagglomerate bacteria clusters or flocs through a number of physical, mechanical and chemical effects arising from cavitation bubbles when sufficient power is applied. However, at low power, ultrasound can also be used to improve the effectiveness of biocides. Past studies showed that neither chlorination nor sonication alone was able to destroy completely the bacteria present. Extending the exposure time of sonication and chlorination dose could enhance the biocidal effect of the individual techniques. The aim of this study is to investigate the effect of exposure time of the ultrasound treatment on the biocidal efficiency of chlorine towards Escherichia coli suspension. An ultrasonic processor with horn sonotrode operating at 20 kHz and 100% amplitude was used in combination with chlorination to treat Escherichia coli. Viable plate count technique was used as a measure of microbial activity and DPD Colorimetric Method determined the residual chlorine. The experiments consisted of three parts: primary disinfection with ultrasound alone, with free chlorine alone and sonication in conjunction with chlorination. For biocidal effect of ultrasound alone, the sonolytic inactivation of Escherichia coli showed that at 20 kHz, the maximum reduction of 4.1 log units of E. coli was achieved after 30 minute sonication. The E. coli decay kinetics pseudo-first order behavior with the rate constant kE.coli = 0.307 min -1 (R 2 = 0.99). For primary disinfection with the free chlorine, maximum reduction of colonies of E. coli of 51.32% has been achieved at 10 mg/L. There was no significant improvement in the disinfection effects of chlorine at two different doses of 10mg.min/L and 50mg.min/L. Ultarsound in conjunction with chlorine significantly reduced the number of bacteria present and the amount of chlorine required for disinfection. The maximum effects of ultrasound with chlorination are achieved such that the colonies of E. coli are reduced by 89.33% by ultrasonic pretreatment for 2 minutes followed by chlorination for 5 minutes. The pretreatment by ultrasound was proven to inactivate more colonies of E. coli than pretreatment by chlorination. However, our ultrasonic processor can only operate at fixed low frequency of 20 kHz, and maximum power of 30W, which limited other options. Thus a different kind of sonicator with high power setting and high frequency should be used to further investigate the inactivation of E. coli.